2017
DOI: 10.1016/j.rbmo.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum markers in predicting successful outcome in expectant management of missed miscarriage

Abstract: The aim of this study was to evaluate the use of biological serum markers, available routinely in most hospital clinical laboratories, in predicting successful outcomes of expectant management in women presenting with a missed miscarriage. This is a single centre observational prospective study over a 16-month period. Among the 490 women who consented to the study protocol, 83 presented with missed miscarriage during the first trimester of pregnancy and opted for expectant management. The mean gestation sac di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…11 Another study also concluded that Hs-CRP did not contribute as a predictor of complications in the early phases of pregnancy. 12 However, the role of CRP in pregnancy has not shown consistent results. The study reported concluded that an abnormal CRP response in the fi rst trimester of pregnancy indicates a disruption in fetomaternal relationships and is associated with the incidence of abortion.…”
Section: Discussionmentioning
confidence: 97%
“…11 Another study also concluded that Hs-CRP did not contribute as a predictor of complications in the early phases of pregnancy. 12 However, the role of CRP in pregnancy has not shown consistent results. The study reported concluded that an abnormal CRP response in the fi rst trimester of pregnancy indicates a disruption in fetomaternal relationships and is associated with the incidence of abortion.…”
Section: Discussionmentioning
confidence: 97%
“…There are only a few studies that have evaluated the relationship between hsCRP and first or second trimester pregnancy loss 34,36 . We have also evaluated its role in predicting successful outcome of expectant management in women presenting with missed miscarriage 37 . Similarly to the present study, we found no significant difference in the mean serum hsCRP levels between women with failed and successful conservative management of TEP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unlikely to be useful in busy emergency departments or early pregnancy units. Memtsa et al reported that the older the patient and the lower the s-progesterone level the higher the likelihood of complete miscarriage < 7 days [18]. We did not test patient age as a predictor, because we found it unlikely to be related to the time to complete evacuation of the uterine cavity.…”
Section: Commentsmentioning
confidence: 94%
“…This is probably explained by differences in study populations (types of miscarriage, symptomatology), definitions of complete miscarriage and treatment success, and variables tested as predictors. However, more than one study reported that the lower the s-β-hCG and s-progesterone values the higher the likelihood of success of expectant management [ 16 , 18 , 19 , 21 ] and that success rate is higher in incomplete miscarriages than in embryonic or anembryonic miscarriages [ 15 17 ]. Only two studies are reasonably similar to ours with regard to inclusion criteria and definition of treatment success [ 18 , 21 ].…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation